The Usefulness Of Management Accounting Information System Characteristics According To The Perception Of Users - Veronica Christina; Sunardi Sembiring Brahmana (Program Studi Ekonomi Pembangunan Fakultas Ekononomi Universitas Simalungun, 2024)
This research aims to describe the benefits of the characteristics of management accounting information in several types of companies in the city of Bandung according to the perceptions of employees in these companies. Management accounting information systems are a type of accounting that is often ignored in various companies. The management of a company certainly requires relevant and accurate information when making decisions, this information is provided by the management accounting information system. The research results show that managers perceive the characteristics of management accounting information in the form of scope, timeliness, and aggregation as more than useful, while the characteristics of integration are considered very useful.